The New Disrupters - McGrath, Rita (MIT Sloan Management Review, 2020)
Clayton Christensen's Theory of Disruptive Innovation presciently explained that fast-moving disrupters entering the market with cheap, low-quality goods could undermine companies wed to prevailing beliefs about competitive advantage. In the last decade, however, disrupters have changed dramatically. They now enter the market with products and services that are every bit as good as those offered by legacy companies - and make it harder than ever for traditional businesses to compete.